A new medium for Caenorhabditis elegans toxicology and nanotoxicology studies designed to better reflect natural soil solution conditions. (13th June 2013) - Tyne, William; Lofts, Stephen; Spurgeon, David J.; Jurkschat, Kerstin; Svendsen, Claus
Abstract: A new toxicity test medium for Caenorhabditis elegans is presented. The test solution is designed to provide a better representation of natural soil pore water conditions than currently available test media. The medium has a composition that can readily be modified to allow for studies of the influences of a range of environmentally relevant parameters on nematode biology and toxicology. Tests conducted in the new medium confirmed that nematodes' reproduction was possible at a range of solution pH levels, offering the potential to conduct toxicity studies under a variety of conditions. A test to establish silver nanoparticle and dissolved silver nitrate toxicity, a study type not feasible in M9 or agar media due to precipitation and nanoparticle agglomeration, indicated lower silver nanoparticle (median effective concentration [EC50] of 6.5 mg Ag/L) than silver nitrate (EC50 0.28 mg Ag/L) toxicity. Characterization identified stable nanoparticle behavior in the new test medium. Environ Toxicol Chem 2013;32:1711–1717. © 2013 SETAC